HUBUNGANANTARA PENYESUAIAN DIRI BELAJAR DI PERGURUAN TINGGI DENGAN INDEKSPRESTASI MAHASISWA JURUSAN TEKNIKSIPILFT UNP - 2164-2169, Silvia Rahyu (Universitas Negeri Padang, 2018)
Abstract—Thisresearchbeginswiththe problemsofnewstudentswhileadaptingtostudyincollege.This researchaimstorevealthecorrelation betweenadjustment incollegelearningwithstudentachievement indexDepartment ofCivilEngineeringFTUNP.Thisresearchisacorrelation researchwiththetotal populationofCivilEngineeringDepartmentFTUNPentryyear2016whichare173student. Thesample inthisstudywere64studentsusingProportional RandomSamplingtechnique.Datacollectedusing questionnaireswithLikertScaleconsistingof5criteria,consistingofpositiveandnegativestatements. Thenumberofitemsintheresearchquestionnaire were38pointsstatement.Analysismetodeofthis researchusingPearsonproductmomentcorrelation, basedontheresultsoftheanalysisfoundthatthere isacorrelation betweenself-adjusting learningincollegewithstudentachievement indexwithvaluesof rhitung of0.434> rtabel0.246. Thatmeans thereisapositivecorrelationbetweenadjustmentofself-study incollegewithstudentachievementindexofcivilengineeringdepartmentFTUNPinthefirstyear. Keywords:Adjustment,College,AchievementIndex